Kla-Jon: The Brave To Be Poor Concept And The Principle Of Changing Lifestyle To Overcome Crisis - Griffiths, Onwipa; Angasinha, Chatwarun (Journal of Dhamma for Life, 2025)
This study aims to examine (1) the concept of KLA-JON (“Daring to Be Poor”) and (2) the principles of life transformation through the KLA-JON approach as a means of overcoming personal crises. Employing a qualitative research methodology, the study integrates both documentary research and fieldwork. The participants consisted of 22 individuals, including resident and non-resident volunteers from the Maitree Dhamma Health Network at Suan Pa Na Boon, as well as Dr. Jaipetch Klajon-(Ajarn Mor Khiew-อาจารย์หมอเขียว). The primary data collection methods included in-depth interviews and participant observation, and the data were analyzed using content analysis techniques. The findings reveal that the KLA-JON philosophy is rooted in Buddhist principles, particularly the teachings that emphasize the reduction and relinquishment of defilements—greed, anger, and delusion—through a life of simplicity, non-attachment, and selfless compassion. The concept has been applied and expanded through the lived experiences of Dhamma health volunteers who embody this philosophy in practice, guided by the Five Precepts (Sīla), the Six Principles of Cordiality (Saraniyadhamm 6), the Communal Sharing System (Satharanabhogi), and the Nine Virtues of a Noble Life (Wanna Kao). Together, these principles cultivate balance in body, mind, and community. Significantly, the concept has been inspired and shaped by Phra Bodhirak (Phra Khru Somana Phothirak), founder of the Asoke community, who initiated the Boon Niyom Economy, a merit-based system grounded in voluntary simplicity, self-restraint, collective effort, and ethical living. His teachings encourage mindful austerity, strict observance of ethical discipline, and the spirit of giving without expectation of return. As a result, resilient and self-reliant communities rooted in compassion and mutual support have emerged. The application of KLA-JON has led to holistic recovery and transformation across five key dimensions: (1) improved physical health through conscious consumption, (2) mental peace and emotional vitality, (3) economic stability based on frugality and self-sufficiency, (4) strengthened social relationships and environmental stewardship through interdependence and reduced resource exploitation, and (5) awakened insight and the ability to confront crises with mindfulness and clarity. Rather than signifying passive acceptance of poverty, KLA-JON represents the courageous, voluntary renunciation of defilements. It is an inner liberation that paves the way toward a life of sustainable happiness, peace, and spiritual well-being—both at the individual and communal levels.